2016
DOI: 10.1016/j.exger.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related arterial telomere uncapping and senescence is greater in women compared with men

Abstract: Telomere uncapping increases with advancing age in human arteries and this telomere uncapping is associated with increased markers of senescence, independent of mean telomere length. However, whether there are sex specific differences in arterial telomere uncapping is unknown. We found that telomere uncapping (serine 139 phosphorylated histone γ-H2A.X in telomeres) in arteries was ~2.5 fold greater in post-menopausal women (n=17, 63±2 yrs) compared with premenopausal women (n=11, 30±2 yrs, p=0.02), while there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…From the existing literature, female sex is associated with reduced capacity for DNA repair in different organs and cell types (Broestl et al, 2022; Kfoury et al, 2018; Malorni et al, 2008; Rall‐Scharpf et al, 2021; Sun et al, 2014; Trzeciak et al, 2008), with one exception to this assumption found by Yousefzadeh et al (2020). Walker et al found that age (>55 y/o) has a greater effect on activating DNA damage response and senescence in aged women compared with aged men (Walker et al, 2016). We found that 150 μM FC significantly increased DNA damage in aged female mouse‐derived CEC, compared with female CEC treated either with 50 μM FC or a vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…From the existing literature, female sex is associated with reduced capacity for DNA repair in different organs and cell types (Broestl et al, 2022; Kfoury et al, 2018; Malorni et al, 2008; Rall‐Scharpf et al, 2021; Sun et al, 2014; Trzeciak et al, 2008), with one exception to this assumption found by Yousefzadeh et al (2020). Walker et al found that age (>55 y/o) has a greater effect on activating DNA damage response and senescence in aged women compared with aged men (Walker et al, 2016). We found that 150 μM FC significantly increased DNA damage in aged female mouse‐derived CEC, compared with female CEC treated either with 50 μM FC or a vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Women have a greater increase in arterial telomere uncapping with age compared with men (32), indicating a possible interaction of aging and menopause. Fasting blood glucose positively correlates with vascular telomere uncapping in women but not in men, whereas systolic blood pressure and pulse pressure positively correlate with vascular telomere uncapping in men but not in women (32). Thus, the rate and causes of vascular telomere uncapping may differ between the sexes.…”
Section: Vascular Telomere Uncapping With Agingmentioning
confidence: 94%
“…However, our knowledge about sex differences in endothelial cellular senescence is very limited. An age-related increase in arterial telomere uncapping and senescence is greater in women than men ( Walker et al, 2016 ), indicating a sex difference in vascular senescence. Future studies should reveal the key players, mechanisms, and signaling pathways about it in both preclinical animal models and human subjects including postmenopausal females and age-matched males.…”
Section: Cellular Senescence Of Endothelial Cellsmentioning
confidence: 99%